2016
DOI: 10.3390/nu8050317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a High-Fat or High-Fiber Diet on Intestinal Microbiota and Metabolic Markers in a Pig Model

Abstract: To further elaborate interactions between nutrition, gut microbiota and host health, an animal model to simulate changes in microbial composition and activity due to dietary changes similar to those in humans is needed. Therefore, the impact of two different diets on cecal and colonic microbial gene copies and metabolic activity, organ development and biochemical parameters in blood serum was investigated using a pig model. Four pigs were either fed a low-fat/high-fiber (LF), or a high-fat/low-fiber (HF) diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 74 publications
3
48
0
2
Order By: Relevance
“…Adolescent pigs fed a 5‐week HFD developed an obese phenotype, having increased body weight and 46% greater back‐fat depth compared with pigs consuming a LFD, which is in agreement with previous findings . Back fat thickness is commonly used as a measure of obesity in pigs , and increased fat deposition is associated with dysregulated gene expression (such as TCF7L2 and leptin) that are high risk susceptibility genes for type 2 diabetes and obesity .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Adolescent pigs fed a 5‐week HFD developed an obese phenotype, having increased body weight and 46% greater back‐fat depth compared with pigs consuming a LFD, which is in agreement with previous findings . Back fat thickness is commonly used as a measure of obesity in pigs , and increased fat deposition is associated with dysregulated gene expression (such as TCF7L2 and leptin) that are high risk susceptibility genes for type 2 diabetes and obesity .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, a recent study in conventional pigs found increased Bacteroidetes ( Bacteroides group and Prevotella spp.) in both cecum and colon of pigs fed a HFD . In obese Ossabaw minipigs, reduced abundance of genera Prevotella and increased abundance of Clostridium were observed in the colon compared with their lean counterparts, analogous to findings in the current study .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Generally microbial Bacteroidetes species such as Bacteroides fragilis (B. fragilis) appear to be generally beneficial to human health via their ability to cleave dietary fiber into digestible short-chain fatty acids, their production of useful polysaccharides, vitamins and their precursors, volatile fatty acids and other nutrients, however, when they escape the confines of a healthy GI tract microbiome they elicit inflammatory systemic pathology with substantial morbidity and mortality [15,[22][23][24]26]. It is well known that diet has a role in regulating the composition, complexity and speciation of the GI tract microbiome -for example species of Bacteroidetes proliferate in animal models fed high fat-cholesterol (HF-C) diets deprived of dietary fiber [25]. Besides their prodigious output of LPS, endotoxins generated by B. fragilis are a leading cause of anaerobic bacteremia and systemic inflammatory distress through the production of the highly pro-inflammatory zinc metalloproteinase B. fragilis toxin (BFT) fragilysin [24,26].…”
Section: Bacteroidetes and Bacterioides Fragilis Abundance And Prolifmentioning
confidence: 99%
“…Related to the points above, overall the GI tract microbiome of AD patients was found to exhibit highly selective abundance and compositional differences in genus and species from control age-and sex-matched individuals and exhibited phylum-and genus-wide differences in bacterial abundance including a significantly increased abundance of Bacteroidetes and decreased abundance of Firmicutes and Bifidobacterium in the AD-affected brain [9,[14][15][16][17][23][24][25][26]. Very recently, at least 2 independent publications have shown an enrichment of LPS within the neocortex or hippocampus of ADaffected brain [6,[27][28][29].…”
mentioning
confidence: 99%